Place-based policies and firm performance: Evidence from Special Economic Zones in India - Holger Görg; Alina Mulyukova (European Economic Review, 2024)
This paper exploits time and geographic variation in the adoption of Special Economic Zones in India to assess the direct effects of the program on firm performance. We combine geocoded firm-level data and geocoded SEZs. Our analysis yields that conditional on controlling for initial selection based on observables, the establishment of new SEZs did not induce any discernible positive effect on the productivity growth of firms in the SEZs. To explain this, we focus on the possibility of distortions through non-profitable activities on the part of managers. We find that firms especially in publicly-owned SEZs decreased their productivity growth, while firms located in privately-owned SEZs experience productivity increases. We also show that directors of firms located inside the publicly-owned zones experienced a significant increase in their salary growth, which is not the case in privately-owned SEZs. Our findings are in line with the idea that the possibility of rent-seeking by managers leads to distortions in program implementation.
Keywords: O18; O25; P25; R10; F21; F60; 330; Special Economic Zones; Firm performance; India